Brca2 and Trp53 deficiency cooperate in the progression of mouse prostate tumourigenesis. - Jeffrey C Francis; Afshan McCarthy; Martin K Thomsen; Alan Ashworth; Amanda Swain (PLoS Genetics)
Epidemiological studies have shown that one of the strongest risk factors for prostate cancer is a family history of the disease, suggesting that inherited factors play a major role in prostate cancer susceptibility. Germline mutations in BRCA2 predispose to breast and ovarian cancer with its predominant tumour suppressor function thought to be the repair of DNA double-strand breaks. BRCA2 has also been implicated in prostate cancer etiology, but it is unclear the impact that mutations in this gene have on prostate tumourigenesis. Here we have undertaken a genetic analysis in the mouse to determine the role of Brca2 in the adult prostate. We show that deletion of Brca2 specifically in prostate epithelia results in focal hyperplasia and low-grade prostate intraepithelial neoplasia (PIN) in animals over 12 months of age. Simultaneous deletion of Brca2 and the tumour suppressor Trp53 in prostate epithelia gave rise to focal hyperplasia and atypical cells at 6 months, leading to high-grade PIN in animals from 12 months. Epithelial cells in these lesions show an increase in DNA damage and have higher levels of proliferation, but also elevated apoptosis. Castration of Brca2;Trp53 mutant animals led to regression of PIN lesions, but atypical cells persisted that continued to proliferate and express nuclear androgen receptor. This study provides evidence that Brca2 can act as a tumour suppressor in the prostate, and the model we describe should prove useful in the development of new therapeutic approaches.